2017
DOI: 10.1111/1753-0407.12544
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age discrepancy of HbA1c and fetal hemoglobin determined by HPLC in a large Chinese Han population

Abstract: The data suggest that sex and age should be considered in clinical interpretation of HbA1c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Additionally, an early Hb level, as with the other blood lines, is very dependent on weeks and increases with weeks [24,25]. This explains the results of our decision tree, i.e., an early Hb threshold of >15.2 would have no independent impact at 24 months on a population that is said to be less at risk (female, VP, >26 weeks), which naturally has a higher sex-related Hb fetal threshold [26]. A recent study confirms this sex-specific association between an early marker of anemia and cognitive function at age 12 months of age and white matter volume [27].…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, an early Hb level, as with the other blood lines, is very dependent on weeks and increases with weeks [24,25]. This explains the results of our decision tree, i.e., an early Hb threshold of >15.2 would have no independent impact at 24 months on a population that is said to be less at risk (female, VP, >26 weeks), which naturally has a higher sex-related Hb fetal threshold [26]. A recent study confirms this sex-specific association between an early marker of anemia and cognitive function at age 12 months of age and white matter volume [27].…”
Section: Discussionmentioning
confidence: 63%
“…A series of studies have also indicated that VI or low visual acuity is more prevalent among Chinese women (general population) ( 28 ). Studies showed that women might have a longer life expectancy, higher HbA1c level ( 29 ), and higher prevalence of DM ( 30 ) than men, which may contribute to their higher risk of developing DM-related ocular complications and age-related ocular disorders ( 22 ). However, whether DM and gender could synergistically affect VI in the Chinese population with DM is yet to be elucidated and deserves further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study uniquely establishes the existence of a strong association between HbA1c, HbA0 and HbA2, which should be explored further to determine possible interference in HbA1c estimation, especially among populations with prevalently higher proportions of the highlighted Hb types. In contrast, another study targeting age-speci c effects of Hb types on HbA1c interpretation reported a rather low degree of correlation between HbF and Hba1c, suggesting that age could be a signi cant factor in the interpretation of HbA1c levels (Hu et al, 2018). Since the analysis was done across patients with various ages with varying glycaemic control capabilities (both types 1 and 2 diabetes mellitus), this could explain the deviation from the ndings of the current study, which only focused on patients with T2DM, which are primarily of adult age.…”
Section: Discussionmentioning
confidence: 90%